Human rights and international relations - Vincent, R. J., 1943- (Cambridge [Cambridgeshire] ; New York : Cambridge University Press, 1986)
This book is about the impact of human rights on the relations among states. It seeks to bring together in one place an account of the theory of human rights (what they are; where they come from; whether they are universal); a discussion of the part they play in contemporary international politics (including East/West and North/South relations); and a view of what ought to be done about them--especially by the Western powers. Dr. Vincent recommends that provision for subsistence rights has a strong claim to priority over other human rights. Dr. Vincent's conclusion neither endorses the notion of the advance of cosmopolitan values in the society of states, nor rests on an observation of the continuing strength of state society. He shows how the grip of the sovereign state might in fact be tightened by its successful co-option of the international doctrine of human rights. Published in association with the Royal Institute of International Affairs.
Introduction -- Part I. Theory: The idea of human rights ; Human rights in Western political thought ; Human rights and cultural relativism -- Part II. Practice: Human rights in East-West relations ; Human rights in North-South relations ; Human rights in contemporary world society -- Part III. Policy: Human rights and the theory of international relations ; Human rights in foreign policy.
"Published in association with the Royal Institute of International Affairs."
Includes bibliographical references (pages 153-178) and index.
Keywords: Civil rights; Human rights; International relations